CLUSTERING METHOD IN ENRICHING STUDENTS’ VOCABULARY MASTERY AT STUDENTS OF UIN ALAUDDIN MAKASSAR - Dewang, Syarif Alqadri; , Kamsinah (ETERNAL (English, Teaching, Learning, and Research Journal), 2017)
The objective of paper was to find out whether or not the use of Clustering Method could enrich the students’ vocabulary mastery of the second semester students at English Education Department Tarbiyah and Teaching Science Faculty UIN Alauddin Makassar. This research employed quasi-experimental design with two group pre-test and post-test design. The population of this research was the second semester students at English Education Department Tarbiyah and Teaching Science Faculty UIN Alauddin Makassar which is consisted of 78 students. The sample of the research consisted of 60 students which was taken by using purposive sampling technique, 30 students were taken as experimental class and 30 students as control class. The instrument of this research was a written vocabulary used in pre-test and post-test. The result of the data indicated that there was a significant difference between students’ post-test in experimental class and control class. The mean score of post-test (69.6) in experimental class was greater than the mean score of post-test (3.8) in control class. The standard deviation of post-test (8.9) in experimental class was lower than the standard deviation of post-test in control class (13.5). From t-test, the researcher found that the value of t-test (1.87) was lower than t-table (2.042) at the level of significance 0.05 with degree of freedom (df) =58. It means that the use of Clustering Method is unable to enrich the students’ vocabulary of the second semester students at English Education Department, Tarbiyah and Teaching Science Faculty, UIN Alauddin Makassar.